Be Civic: Educating Young Malaysians On Being Civic Minded Using Mobile Application - JAAFAR, ROSLINAWATI (Journal of Computing Technologies and Creative Content, 2019)
This study was designed as a solution towards the lack of mobile game application in Malaysia in teaching preschool students on behaving civic minded. The mobile game application will consists of 3 levels of scenarios such as Kindergarten, Home and Playground levels which mimic the typical surroundings that preschool aged 4 to 6 years old will encounter on daily basis. The idea of the gameplay of this mobile application game is for students to quickly pick up toys or trash lying around on those 3 scenarios within the given time. In return, hopefully that kind of gameplay will train preschool students on behaving accordingly in the future. All of the elements of multimedia is incorporated in this mobile game application to suit the preschool students cognitive needs and game trends.